KEDUDUKAN ANAK LUAR KAWIN DALAM HUKUM WARIS - Angelin, Margareta Sevilla Rosa; Putri, Farida Danas; Sanduan, Akbar Prasetyo (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract The purpose of the research from this journal is to determine how the position of extramarital child in inheritance law applies in Indonesia. Then afterwards, it will appear how the inheritance law in the Indonesian state regulates the inheritance rights of the out-of-wedlock child. From this research, various problems will also arise that arise as a result of the position of extramarital children who have inheritance rights which must also be recognized, which will then be offered solutions through this journal research based on the laws and regulations that have legally regulated it. The purpose of marriage is to form a happy, eternal and prosperous family. A harmonious family life also arises when a child is blessed. However, some people prefer to have children without a marriage bond. This causes problems in terms of inheritance distribution. In this matter it has been conveyed in accordance with Law Number 1 of 1974 concerning marriage, many have touched on family issues which are closely related to a basis of marriage as Article 1, that: